Generation Z and organizational citizenship behavior of sharia banking - Ahyar Yuniawan; Eldes Willy Filatrovi; Iqbal Arraniri (Jurnal Siasat Bisnis, 2021)
Purpose: The goal of this study is to test and examine the effect of organizational support on employee engagement and OCB; the impact of career development on employee engagement and OCB; as well as the impact of employee engagement on OCB. The survey was carried out on Indonesia's 200 Sharia Banking Generation Z employees.Design/methodology/approach: All Generation Z employees working as the population in Islamic banking companies in Indonesia use the questionnaire and interviews to collect data. The purposeful sampling was used in this study where the researcher understood that it was possible to gather the appropriate information from a particular population that was able to provide the information requested and that the predetermined criteria had been fulfilled. Since the population is too large, this method was chosen. 200 samples consist of the sample number. In this analysis, SEM is the method used to process information (Structural Equation Model)Findings: The organizational support variable is shown to be capable of influencing employee engagement, which means that the better organizational support offered by the company would also increase the greater engagement of Generation Z employees in Sharia banking. Variables in work growth can affect employee engagement, meaning that the greater company's career development, the greater employee's engagement. Organizational support has been shown to affect OCB, which shows that the better organizational support of the corporation, the greater organizational citizenship behavior of the employee. It is seen that career development is capable of impacting OCB, which means that the greater employee's additional position operation will bring  a stronger implementation of career development. The employee engagement variable has also proven to be able to influence OCB, which means that the greater employee engagement, the greater additional role of Generation Z employees in Islamic banking.Research limitations/implications: Limitations in this study include the nature of open-ended questions which are less understood by respondents, so that many respondents responded with inappropriate answers and some others were not filled in causing the lack of information obtained about the actual situation in current Islamic banking. With this limitation, it is hoped that further scientific research will be considered and made to obtain better research results.Practical implications: The organization would concentrate more on progress in the career development system, taking into account, among other considerations, other variables. Organizations could try to shape their identities as responsible corporate or global citizens by taking a leadership position in sustainable business practices and demonstrating to millennials that OCB is an important way to meet their service needs. The millennial workers would welcome these events, which would encourage them to take on additional duties by assisting other colleagues. Such efforts will be necessary in the twenty-first century to build an effective workforce.Originality/value: It has been shown that employee engagement as an intervening variable can mediate the impact on organizational citizenship behavior between organizational support and career growth, although calculations show that the direct effect of independent variables (organizational support and career development) on OCB is greater than that through employee engagement variable (indirect influence)